Abiotic stress induced changes in protein quality and quantity of two bread wheat cultivars. (May 2016) - Labuschagne, M.T.; Moloi, J.; van Biljon, A.
Abstract: Protein quantity and quality of wheat flour have been found to be influenced by abiotic stress conditions. The aim of this study was to determine the effect of heat, drought and cold stress on protein quantity and quality using reverse phase and size exclusion high performance liquid chromatography in two bread wheat cultivars. Heat stress caused a significant increase in protein content of both cultivars, while drought stress caused a significant protein increase in Duzi. Sodium dodecyl sulphate (SDS) soluble large monomeric proteins were significantly increased by heat stress in both cultivars, and SDS insoluble large polymeric proteins were significantly increased by heat and drought stress in Kariega. SDS insoluble small polymeric proteins were significantly decreased by all three stress conditions in Duzi and heat stress in Kariega. Heat and drought stress had similar effects on protein, but cold stress caused different effects. GluD1 subunit 2 was least influenced by stress conditions, but GluD1 subunit 12 was significantly reduced by all stress conditions. GluA1 subunit 2* and GluB1 subunit 17 were significantly increased by heat and drought in Kariega. Heat stress had the largest effect on protein quality and quantity, and there was a large genotype effect. Highlights: Heat stress significantly influenced protein quality and quantity. Drought stress had a similar but smaller effect than heat on protein. Cold stress had very different effects on protein compared to heat and drought. There was a strong genotype effect in reaction to stress conditions.